Analisis Kebudayaan Batak Pakpak di Sumatera - Nur Sakinah; Dewi Hanifah; Dian Novianti Sitompul (EduInovasi: Journal of Basic Educational Studies, 2024)
Batak Pakpak regional culture is an integral part of the richness of Indonesian culture spread across the Sumatra region. Geographically, the Pakpak Batak tribe inhabits the high hilly areas around the North Tapanuli area. Their culture encompasses various aspects, including language, customs, traditional arts, music, dance, and unique beliefs and value systems. The customs of the Pakpak Batak tribe are very strong in everyday life, with norms that regulate various aspects of social, economic and religious life. Traditional arts such as carving, weaving and stone carving are deep cultural expressions and have high value for the Pakpak people. Apart from that, traditional Batak Pakpak music and dances, such as gondang sabangunan and tortor, are important media in traditional ceremonies and cultural festivals. They are also known for their beliefs and value systems that value living in harmony with nature and the continuity of generations. This research aims to dig deeper into the cultural diversity of the Batak Pakpak in Sumatra and understand the role and cultural values in strengthening their identity. Through this analysis, it is hoped that it can provide a more comprehensive picture of this cultural richness and its implications in the context of Indonesia's cultural diversity.